Private Provision of a Public Good : Social Capital and Solid Waste Management in Dhaka, Bangladesh - Pargal, Sheoli; Gilligan, Daniel; Huq, Mainul (World Bank, Washington, DC, 2015)
The authors try to identify the determinants of private, community-based provision of a public good - in this case, trash collection. Using survey data for Dhaka, Bangladesh, where some neighborhoods have successfully organized an alternative to the municipal trash collection service, they examine why some communities or neighborhoods display such initiative, while others do not. Their results show that social capital - trust, reciprocity, and sharing - is an important determinant of whether alternative systems arise in Dhaka. More generally, public-private partnerships, or self-help schemes appear more likely to succeed in neighborhoods high in social capital. Other measures of homogeneity of interests are also important. So, interestingly, is the nature of associational activity. Finally, education levels are strongly, and robustly associated with the existence of collective action for trash disposal. How can policymakers encourage such activity? The process through which community residents start cooperating for the common good, is a function of the strength of their relationships. Government attempts to initiate the process, are therefore unlikely to boost social capital directly, but by lowering information, and transaction costs, they may facilitate a virtuous cycle of successful cooperation, and strengthening social ties.